2018
DOI: 10.1007/s13258-018-0733-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of Hanwoo and Chikso populations using the BovineSNP50 genotyping array

Abstract: Hanwoo and Chikso are classified as Korean native cattle breeds that are currently registered with the Food and Agriculture Organization. However, there is still a lack of genomic studies to compare Hanwoo to Chikso populations. The objective of this study was to perform genome-wide analysis of Hanwoo and Chikso populations, investigating the genetic relationships between these two populations. We genotyped a total of 319 cattle including 214 Hanwoo and 105 Chikso sampled from Gangwon Province Livestock Techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…During wet aging, a * values of rump from both breeds significantly decreased (Figure 1c), following the results of the study performed by Ma et al [21]. This was possibly due to the reduced color stability by the oxidation of myoglobin and lipids [20].…”
Section: Meat Colorsupporting
confidence: 82%
See 3 more Smart Citations
“…During wet aging, a * values of rump from both breeds significantly decreased (Figure 1c), following the results of the study performed by Ma et al [21]. This was possibly due to the reduced color stability by the oxidation of myoglobin and lipids [20].…”
Section: Meat Colorsupporting
confidence: 82%
“…This was possibly due to the reduced color stability by the oxidation of myoglobin and lipids [20]. It was also reported that extended vacuum storage would deteriorate color stability and bloom development of meat [21]. Meanwhile, a major difference in meat color between Hanwoo and Chikso rump was found in a * value.…”
Section: Meat Colormentioning
confidence: 99%
See 2 more Smart Citations
“…Song et al. (2018) observed that this gene was associated with carcass quality traits in native Korean cattle (Hanwoo and Chikso). LRP1B mediates the lipid transport process of apolipoprotein E, which is involved in cholesterol transport, and also participates in other physiological processes, such as the transport of nutrients and vitamins, and neurological development (May et al., 2007).…”
Section: Discussionmentioning
confidence: 99%